2019
DOI: 10.1519/jsc.0000000000002346
|View full text |Cite
|
Sign up to set email alerts
|

Application of Change of Direction Deficit to Evaluate Cutting Ability

Abstract: Th e a p plic a tio n of c h a n g e of di r e c tio n d eficit t o e v al u a t e c u t ti n g a bility C u t h b e r t , M, Do s' S a n t o s, T, T ho m a s, C a n d Jon e s, PA h t t p:// dx. doi.o r g/ 1 0. 1 5 1 9/JSC.0 0 0 0 0 0 0 0 0 0 0 0 2 3 4 6 Ti t l e Th e a p plic a tio n of c h a n g e of di r e c tio n d eficit t o e v al u a t e c u t ti n g a bility A u t h o r s C u t h b e r t, M, Do s ' S a n t o s , T, Tho m a s , C a n d Jon e s, PA Typ e Articl e U RL This ve r sio n is a v ail a bl e a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…Moreover, Loturco et al [15] found a statistically significant large positive relationship between 100 • COD deficit and 10-m flying start linear sprint. Unfortunately, Loturco and colleagues [16] did not assess whether these results would be similar in the case of a linear sprint from the standing start. At the same time, Loturco et al [28] revealed differences in the COD deficit between elite soccer players versus handball, rugby and futsal players.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Loturco et al [15] found a statistically significant large positive relationship between 100 • COD deficit and 10-m flying start linear sprint. Unfortunately, Loturco and colleagues [16] did not assess whether these results would be similar in the case of a linear sprint from the standing start. At the same time, Loturco et al [28] revealed differences in the COD deficit between elite soccer players versus handball, rugby and futsal players.…”
Section: Discussionmentioning
confidence: 99%
“…The solution that can shed new light on the assessment of COD ability, is a measurement of COD deficit. However, to date little attention has been given to the relationship between COD deficit and the performance of the high-intensity actions and COD tests [2,10,15,16]. The COD deficit is an additional time that athletes need, to complete running with a COD in comparison to straight-line sprint at the same distance (e.g., athlete's 20-m sprint time is subtracted from the 20-m COD time).…”
Section: Introductionmentioning
confidence: 99%
“…The 90°COD performance was measured by the total running time to complete the 5 m + 5 m course (COD t ), and the fastest trial of each direction was used for further analysis. Furthermore, COD deficit (COD d ) was calculated by subtracting the 10-m sprint time from the COD t ( Cuthbert, Dos’Santos & Jones, 2019 ; Nimphius et al, 2016 ; Trecroci et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In soccer, a number of COD tests have been proposed to monitor COD ability, such as 505 test, modified Illinois COD test, COD and acceleration test, and modified agility T -test ( Cuthbert, Dos’Santos & Jones, 2019 ; Dos’Santos et al, 2019b ; Hachana et al, 2014 ; Lockie et al, 2013 ; Loturco et al, 2019 ; Loturco et al, 2018 ; Sassi et al, 2009 ; Sporis et al, 2010 ). Most of them use the total time to complete the test as an actual measure of the players’ COD ability.…”
Section: Introductionmentioning
confidence: 99%
“…These contradictions could be solved by introducing the concept of deficit in COD, where COD action is isolated from linear action within the tests [ 53 ]. While several studies [ 54 , 55 ] have shown the relationship of CODs to the deficit itself, no considerations have been made with linear velocity. Although some authors [ 56 ] still suggest linear velocity to be a determining factor for COD performance, high COD approaching velocities may increase the loads which the knee receives in valgus.…”
Section: Discussionmentioning
confidence: 99%